Existence of solutions for a parabolic equation in bounded domain. Issue 3 (17th February 2018) - Ghanmi, A.; Kenzizi, T.
Abstract: In this paper, we study the existence of nonnegative solutions for the parabolic problem where D is a smooth domain of, ( ), the function is such that and is the normalized positive eigenfunction corresponding to the first eigenvalue of and V belongs to a class of time-dependant potentials which can be written as a nonlinear combination of derivatives of a function.